Psychological skills assessment and referee rugby sevens performance - Mohamad Nizam Nazarudin; Mohamad Razali Abdullah; Mohd Sofian Omar Fauzee; Nagoor Meera Abdullah; Hasnol Noordin, 671124105267; Pathmanathan K. Suppiah (2014)
This study aims to examine the psychological skills that are commonly used among referees rugby sevens and their relationship with referees’ performance. The Psychological Skills Inventory for Sports (Mahoney, Gabriel, & Perkins, 1987) was adapted and modified specifically for use by rugby sevens referees. It was administered to 132 rugby sevens referee (mean age 33.4 + 1.5 years; 132 males) of the Malaysian Rugby Union (MRU) which has been refereed in 10 rugby sevens tournament in Malaysia. The psychological skills variables employed in the questionnaire included confidence, anxiety management, mental preparation, motivation and concentration. The IRB Referee Sevens Performance Evaluation Form (r=0.94) was used to evaluate referee performance. These instruments measure the performance variable that contains the dimensions of control, communication, application of the law and the positioning. The descriptive statistics of the variables are Psychological skills (M= 120.14, SD= 6.97) and performance (M= 136.45, SD= 4.47) identified at a moderate level. Findings indicated no significant differences [F= (3, 72) =.636, p>0.05] in psychological skills across age levels but there are significant differences [F= (3, 128) =57.616, p<0.05] across experience levels. Highly experienced referees scored significantly higher in all psychological constructs compared to less experienced referees. Variables that showed strong and positive relationships with performance were anxiety management (r= .61), concentration (r= .57), confidence(r= .54) and motivation (r= .50). In conclusion, the psychological skills assessment can improve the efficacy of rugby referees and recommends that referee coaches increase the use of psychological skills in competitions and future training. Researchers should investigate the effectiveness of applied sport psychology interventions in enhancing referee performance in the future.